2021
DOI: 10.1002/fsn3.2421
|View full text |Cite
|
Sign up to set email alerts
|

Variations on gut health and energy metabolism in pigs and humans by intake of different dietary fibers

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 96 publications
1
19
0
Order By: Relevance
“…However, when supplemented with FOS, a significant growth of beneficial bacteria, namely Lac, Bif, and CIV (24 and 48 h) and Bac (48 h) was observed, in comparison with SKM only (p < 0.05) (Figure 1 and Table S1). These results are somehow expected, as their beneficial properties and role in human nutrition, health and energy metabolism of FOS are currently well-established [43,63,64]. The most acknowledged nutritional effect of FOS is the selective stimulation of Bif and Lac growth/activity and the prevention of harmful bacteria colonization such as E. coli and Salmonella typhimurium in the human colon [17,41,63,65].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, when supplemented with FOS, a significant growth of beneficial bacteria, namely Lac, Bif, and CIV (24 and 48 h) and Bac (48 h) was observed, in comparison with SKM only (p < 0.05) (Figure 1 and Table S1). These results are somehow expected, as their beneficial properties and role in human nutrition, health and energy metabolism of FOS are currently well-established [43,63,64]. The most acknowledged nutritional effect of FOS is the selective stimulation of Bif and Lac growth/activity and the prevention of harmful bacteria colonization such as E. coli and Salmonella typhimurium in the human colon [17,41,63,65].…”
Section: Discussionmentioning
confidence: 93%
“…The main SCFA are acetate, propionate, and butyrate, which together represent 90-95% of the total SCFA, and at a smaller concentration (~5% of total SCFA) are the BCFA, such as isobutyrate and isovalerate [66,67]. The production of SCFA improves the gut health through the promotion of the microbial growth and microbial community structure (by balancing the interactive competition between "beneficial" and "harmful" bacteria), the secretion of bacteriocin, and the enhancement of the immune barrier [64,[66][67][68][69][70]. These SCFA are also important as physiological signaling molecules, adjusting biological processes related with the host's health and diet, playing a key-role in regulating responses of the gut microbiota fermentation to the host's metabolism [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propionic acid is produced mainly by Bacteroidetes ( 43 ), and butyric acid is produced mainly by Firmicutes , providing a metabolic energy source for intestinal cells. SCFAs have anti-inflammatory effects, help maintain the integrity of the mucosal barrier, are associated with the regulation of the immune response, help maintain the homeostasis of intestinal microorganisms ( 44 ), and reduce the risk of colon cancer ( 45 ). Recharla's research showed that propionic acid, butyric acid and acetic acid were positively correlated with most bacteria ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The greatest bacterial density in broilers is found in the cecum ( Rehman et al, 2007 ). A complex microbial community in the intestine plays a key role in nutrition and health ( Yang and Zhao, 2021 ). For example, probiotics and their metabolites can promote a symbiotic balance of microorganisms in the gut of the broilers ( Perez-Chabela et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%